Upaya Pengenalan Media Pembelajaran Ular Tangga 3D - Amrini Shofiyani; Nurul Hidayah; Muhammad Yasin Fatchul Barry; Dzikrul Hakim Al-Ghozali; Hafif Azizah; Nur Herlina; Zayyana Fajar Febriana Nur; Muhammad Romadhon; Muslimin Muslimin (Al-Tafani: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
This academic article explores the implementation of a 3D Snake and Ladder as an innovative learning medium in the context of community empowerment in education. Authored by Amrini Shofiyani and team from Universitas KH. A. Wahab Hasbullah, the study addresses the prevalent issue of a lack of engaging learning media faced by students, particularly in Desa Kauman, Kecamatan Mojoagung, Kabupaten Jombang, Provinsi Jawa Timur. The article introduces the concept of 3D Snake and Ladder as a game-based learning tool, aiming to enhance students' interest, teamwork, and cognitive skills. The Game Based Learning approach is employed as a method for the training program, conducted with students from MI Sulaimaniyah. The results indicate a high level of practicality, with an average percentage of 89.7% based on students' responses to the 3D Snake and Ladder learning medium. The study contributes to providing an engaging and effective learning experience for students, fostering motivation and curiosity.